Various interventions for cancer-related fatigue in patients with breast cancer: a systematic review and network meta-analysis - Li, Ying; Gao, Lei; Chao, Yaqing; Lan, Tianhao; Zhang, Jie; Li, Ruoqi; Zhang, Zerui; Li, Shuming; Lian, Jing; Wang, Zhaofeng; Chen, Xiaoan (Frontiers in Oncology, 2024)
To investigate the effects of various intervention approaches on cancer-related fatigue (CRF) in patients with breast cancer.Computer searches were conducted on PubMed, Embase, Cochrane Library, Web of Science, China National Knowledge Infrastructure (CNKI), China Science and Technology Journal Database (VIP), and Wanfang databases from their establishment to June 2023. Selection was made using inclusion and exclusion criteria, and 77 articles were included to compare the effects of 12 interventions on patients with breast cancer. Results Seventy-seven studies with 12 various interventions were examined. The network findings indicated that cognitive behavioral therapy (CBT) (SMD, -1.56; 95%CI, -3.08~-0.04), Chinese traditional exercises (CTE) (SMD, -0.85; 95%CI, -1.34~-0.36), aerobic exercise (AE) (SMD, -0.77; 95%CI, -1.09~-0.45), multimodal exercise (ME) (SMD, -0.75; 95%CI, -1.26~-0.25), music interventions (MI) (SMD, -0.74; 95%CI, -1.45~-0.03), and yoga (YG) (SMD, -0.44; 95%CI, -0.83 to -0.06) can reduce CRF more than the control group (CG). For relaxation exercises (RE) (MD,